Ethics, present time and memory in Brazilian journals of history, 1981-2014 - Avelar, Alexandre; Pereira, Mateus Henrique de Faria (Historein, 2018)
The goal of this article is to present a portrait of the “state of the art” of memory, present time and ethics discussions in Brazilian academic journals of history (1981-2014), with an emphasis on the years 2010-2014. The article is organized in individual sections, for each key theme, followed by some brief remarks by way of conclusion. We decided to write our main observations on the studied sources and our methodology from the start, to provide the reasons behind our choices and exclusions. Our aim in this study is to reflect on two questions: regarding the studies on ethics, present time and memory, is there any “Brazilian peculiarity”? Is it possible to outline some central characteristics and trace them back to their main influences and references?